LEGAL PROTECTION FROM NUCLEAR WEAPONS WITH AN EMPHASIS ON MARINE ENVIRONMENTAL PROTECTION - Jerolim Ostojić (Zbornik Radova Pravnog Fakulteta u Splitu, 2008)
Nuclear weapons can be the reason for much dangerous pollution of the environment. The consequences of nuclear testing, explosion of atom bombs in Hiroshima and Nagasaki and various nuclear accidents all bear witness to this. Nuclear weaponry falls into the category of weapons for mass destruction, together with bacteriological (biological), chemical and similar weapons. That fact alone clearly points out how important it is to prevent the use and production of such weapons. One of the means is certainly legal regulation on a global level. Included here is the damage of boats in nuclear manufacture, that is, vessels and aircraft which carry nuclear weapons, not to mention also the possible war or terrorist and diversant acts with nuclear weapons and matter. The fact that the very nuclear substance per se can be and is nuclear weaponry because of its very dangerous properties should certainly be emphasised. Similarly, the UN General Assembly in New York on 13 April 2005 approved a new agreement on the fi ght against terrorism which will compel the government to punish those who illegally possess nuclear equipment or radioactive material. The Agreement was offered for signing on 14 April that same year. For it to come into force, 22 countries had to ratify it. The document was conciliated after seven years of negotiations and it is the 13th convention on the fi ght against terrorism and the fi rst completed after the terrorist attack on the USA on 11 September 2001. Even though the pollution of the marine environment is mainly regulated by international legal instruments by which pollution from sunk vessels and aircraft and from mainland sources are regulated, agreements which are related to nuclear weapons are also very important, be they related to nuclear experiments or to the prohibition of the use of these weapons, that is, disarmament.